The Idealization of Risk-Profit Sharing in Partnership-Based Sukuk (Islamic Bonds): Why Sukuk Are Experiencing Default? - Rafisah Mat Radzi; Amir Bin Shaharuddin (Academy of IRMBR, 2024)
Non-Indexed Publication